The New Hypostasis of “The Philosophical Brigade” of Todor Pavlov - Najdenov, Georgi (Research Papers, 2018)
The study of Ivaylo Znepolski for the activity of the Todor Pavlov’s "philosophical brigade" in Sofia University "St. Kliment Ohridski" and in the Philosophical Institute of the Bulgarian Academy of Sciences in the 1960s and 1970s is presented. It is shown why, after losing its positions in the 1970s, in the late 1980s and early 1990s, Todor Pavlov's "philosophical brigade" strengthened with a new generation and restored its active activity in the Philosophical Faculty. One particular situation is investigated – the ideological censure practiced by Todor Pavlov's "philosophical brigade" during the Jubilee Conference of Department of Sociology in 2017.
Keywords: Ideological censure; Todor Pavlov's philosophical brigade; Communist establishment; Ideological and political “cradle”